Alat Pendeteksi dan Notifikasi Kerusakan pada Gardu Distribusi PLN - Muhammad Irmansyah; Yul Antonisfia; Amril Amril; Era Madona; Zhefry Anovra (Prosiding SISFOTEK, 2018)
PLN distribution transformer is a transformer as a voltage-lowering from medium to low voltage which will distribute to customers. In some cases, officers are usually constrained by unpredictable disturbances, especially in power distribution networks to customers which disturbed suddenly and on the distribution station itself which caused the supply of power from the main station are not distributed to area or customers are not supply electrically. In this research is designed a device to improve the officers performance in maintenance and repaired on the network. This device use to detect and give notification of information damage on the FCO (Fuse Cut Out) distribution station based microcontroller through sms. This tool is intended to lighten the duty of PLN officers. This tool is installed inside the distribution station transformer. This system operates if the sensor detects the network outages or damage or trips on one of the distribution station transformer along the network. Due to the position of the tool installed on the end of distribution station, so the tool can detect the interference or damage occurs along the network. The tool will send the information data to the officer via sms.